Farewell Lord Jeffrey Amherst: Debate over Amherst College's institutional anchorage in history (Respond to this article at http://www.therai.org.uk/at/debate). Issue 4 (August 2014) - Fernandez, James; Herzog, John
<x xml:space="preserve">Abstract</x> Over the last quarter century or more there has been continuous debate in American colleges and universities over the use of icons and mascots as identity markers and subjects of dramatized playing field appearances and of rouse songs. For the most part these icons and mascots have been essentialized American Indians. The Amherst case is unique. The icon, mascot and song subject is an historical figure, Lord Jeffrey Amherst, the British general ultimately victorious in the French and Indian Wars of the mid‐18th century in America. Recently there has been considerable debate at Amherst College about General Lord Amherst as an appropriate icon because he is also associated with a failed Indian policy and the genocidal use of smallpox blankets against the Indians. He has long been in disrepute for these actions among anthropologists specializing in Native American studies and among historians of the 18th century in America. This article examines the historical reasons for the present debate and the principal differences at play.